Joao Antonio and the staging of a scene in O Jogo da Vida - Martins, Gilberto Figueiredo [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2024)
Joao Antonio Ferreira Filho (1937-1996) created a sort of trilogy, in which the genres of short story and essay are mixed, to develop his thesis that snooker is also a copy of our society. This article accepts the provocation and traces the images and arguments put on the (green) table by the writer from Sao Paulo, comparing them to others, produced by academic thinkers who focused on discussing the sociological and anthropological configuration of the game and playing. Finally, the most narrative of the three texts, the short story Malagueta, Perus e Bacanaco, is compared to its filmic recreation, the feature film O jogo da vida, directed by Maurice Capovilla.
Keywords: Joao Antonio; Snooker and Literature; Maurice Capovilla (cinema)